Mechanical Properties of 17-4 PH Stainless Steel Manufactured by Atomic Diffusion Additive Manufacturing - Animesh Kumar Basak; Jasim Mohammed Sali; Alokesh Pramanik (Designs, 2025)
Atomic diffusion additive manufacturing (ADAM) is a specialized extrusion-based metal additive manufacturing (MAM) process where metal parts are produced through a three-stage process of printing, de-binding and sintering. Several scientific facts, such as dimensional error, surface quality, tensile behavior and the internal structure of this process for specific materials for certain conditions, are not well explained in the existing literature. To address these issues, the present manuscript investigates the effect of infill type and shell thickness on 17-4 precipitation-hardened (PH) stainless steels on the dimensional accuracy, surface roughness and mechanical properties of the printed specimens. It was found that the strength (maximum ultimate tensile strength up to 1049.1 MPa) and hardness (290 HRB) of the specimens mainly depend on shell thickness, while infill type plays a relatively minor role. The principle of atomic diffusion may be the reason behind this pattern, as an increase in shell thickness is essentially an increase in the density of material deposited during printing, allowing more fusion during sintering and thus increasing its strength. The two different infill types (triangular and gyroid) contribute towards minimal changes, although it should be noted that triangular specimens exhibited greater ultimate tensile strength, whereas the gyroid had slightly longer elongation at break. Dimensional accuracy and surface roughness for all the specimens remain reasonably consistent. The cross-section of the tensile tested specimens revealed significant pores in the microstructure that could contribute to a reduction in the mechanical properties of the specimens.